Serum lipopolysaccharide neutralizing capacity in ischemic stroke - Leskelä, Jaakko; Pietiäinen, Milla; Safer, Anton; Lehto, Markku; Metso, Jari; Malle, Ernst; Buggle, Florian; Becher, Heiko; Sundvall, Jouko; Grau, Armin J.; Pussinen, Pirkko J.; Palm, Frederick (PloS one, 2020)
Periodontitis is associated with increased serum lipopolysaccharide (LPS) activity, which may be one mechanism linking periodontitis with the risk of cardiovascular diseases. As LPS-carrying proteins including lipoproteins modify LPS-activity, we investigated the determinants of serum LPS-neutralizing capacity (LPS-NC) in ischemic stroke. The association of LPS-NC and Aggregatibacter actinomycetemcomitans, a major microbial biomarker in periodontitis, was also investigated. The assay to measure LPS-NC was set up by spiking serum samples with E. coli LPS. The LPS-NC, LPS-binding protein (LBP), soluble CD14 (sCD14), lipoprotein profiles, apo(lipoprotein) A-I, apoB, and phospholipid transfer protein (PLTP) activity, were determined in 98 ischemic stroke patients and 100 age- and sex-matched controls. Serum and saliva immune response to A. actinomycetemcomitans, its concentration in saliva, and serotype-distribution were examined. LPS-NC values ranged between 51-83% in the whole population. Although several of the LPS-NC determinants differed significantly between cases and controls (PLTP, sCD14, apoA-I, HDL-cholesterol), the levels did not (p = 0.056). The main determinants of LPS-NC were i) triglycerides (β = -0.68, p<0.001), and ii) HDL cholesterol (0.260, <0.001), LDL cholesterol (-0.265, <0.001), PLTP (-0.196, 0.011), and IgG against A. actinomycetemcomitans (0.174, 0.011). Saliva A. actinomycetemcomitans concentration was higher [log mean (95% CI), 4.39 (2.35-8.19) vs. 10.7 (5.45-21) genomes/ml, p = 0.023) and serotype D more frequent (4 vs. 0%, p = 0.043) in cases than controls. Serotypeablity or serotypes did not, however, relate to the LPS-NC. Serum LPS-NC comprised low PLTP-activity, triglyceride and LDL cholesterol concentrations, as well as high HDL cholesterol and IgG against A. actinomycetemcomitans. The present findings let us to conclude that LPS-NC did not associate with stroke.